2015
DOI: 10.3174/ajnr.a4567
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Features and Expression of Vascular Endothelial Growth Factor Stratify Survival Outcomes in Patients with Glioblastoma

Abstract: BACKGROUND AND PURPOSE: Vascular endothelial growth factor is a well-known tumor-specific biomarker that mediates angiogenesis in glioblastoma via hypoxia-dependent mechanisms. Our aim was to investigate the correlation of clinical characteristics, radiologic features, and vascular endothelial growth factor expression with survival outcomes in patients with glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Previous studies have revealed that PFS can be predicted by several conventional observable MRI features (e.g., tumor contrast enhancement pattern,( Wang et al, 2016a ) peritumoral edema ( Wang et al, 2016b ), and tumor location ( Wang et al, 2017 )) in certain subgroups of glioma. Additionally, a series of correlations has been found between PFS in patients with gliomas and voxel-based imaging features, such as the maximum relative cerebral blood volume value ( Bisdas et al, 2009 ) and the minimum apparent diffusion coefficient ( Romano et al, 2013 ) of a single voxel in the tumor region.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that PFS can be predicted by several conventional observable MRI features (e.g., tumor contrast enhancement pattern,( Wang et al, 2016a ) peritumoral edema ( Wang et al, 2016b ), and tumor location ( Wang et al, 2017 )) in certain subgroups of glioma. Additionally, a series of correlations has been found between PFS in patients with gliomas and voxel-based imaging features, such as the maximum relative cerebral blood volume value ( Bisdas et al, 2009 ) and the minimum apparent diffusion coefficient ( Romano et al, 2013 ) of a single voxel in the tumor region.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of a gadolinium-based contrast agent is a widely utilized method for assessing patients with intracranial neoplasms [9][10][11][12][13]. While there have been studies to understand the physiologic processes underlying contrast enhancement (CE), these efforts largely relied on qualitative assessment and involved limited number of patient samples [14][15][16][17][18]. Some established associations with contrast enhancement in GBM include downregulation of proteins maintaining the BBB (e.g., tight junction protein-2) [16], and overexpression of genes associated with the hypoxia-angiogen esis-edema pathway (e.g., Vascular Endothelial Growth Factor [VEGF]) [16,17,19] and extracellular matrix destruction/tumor cell invasion (e.g., matrix metalloproteinase-7 [MMP7]) [20].…”
Section: Introductionmentioning
confidence: 99%
“…As the tumor develops, it may activate secondary angiogenic pathways, such as bFGF, TGF, and PDGF. GBMs exhibit high levels of VEGF [76]. Higher vascular permeability leads also to radiologic postcontrast enhancement.…”
Section: Most Frequent Genetic Alterations Of Gbmmentioning
confidence: 99%
“…In such tumors, the gross total resection is easier to obtain. High expression of VEGF is associated with poor prognosis, but there are other factors determining prognosis, such as the extent of resection [76].…”
Section: Most Frequent Genetic Alterations Of Gbmmentioning
confidence: 99%